Fitting multiphasic logistic functions to the lactation curves of Gir x Friesian crossbred dairy cattle in Malaysia - Majid, A.M.; Shariff, A.A.; Merican, A.F.; Bong, Y.B. (Penerbit Universiti Kebangsaan Malaysia, 2013)
The data used in this study consisted of milk yield (kg) taken at approximately fortnightly intervals from Gir x Friesian crossbred dairy cattle raised at Institut Haiwan Kluang, Malaysia. The data were first edited, smoothed and then fitted with mono-, di- and triphasic logistic functions. In general, parameter estimates for the first lactation were reasonable. However, for the second lactation the estimates were erratic and unreasonable because this was an atypical lactation for which the multiphasic functions were obviously unsuitable. Residual mean squares for the di- and triphasic functions of the first lactation were very similar (0.0002 and 0.0004, respectively) and smaller than for the monophasic function (0.0894). For the second lactation, residual mean squares for the triphasic function (0.001) was the lowest compared to those for the mono- and diphasic functions (0.0345 and 17 0.0315). For the first lactation, the monophasic function did not fit the data well because it had large residuals. The di- and triphasic functions were almost similar in fitting the lactation and had low residuals. For the second lactation, both the mono- and diphasic functions did not fit the data very well and had rather large residuals. The triphasic function was the most fitting and had small residuals. Derived functions were generally lower for the first lactation than for the second lactation: initial milk yields (4.88 to 6.0 kg versus 9.9 to 11.8 kg); peak milk yields (5.8 to 9.6 kg versus 12.8 to 15.7 kg) and 305-day milk yields (1147.7 to 1328.6 kg versus 1687.4 to 2296.1 kg).